Movement to Another Place. Cultural Expressions of Migration as Source of Reflection Contributing to Social Theory - Slobodan Dan Paich (Culture e Studi del Sociale)
Methodologies are explored to enriching migration theory, with an inter-disciplinary look into cultural expressions resulting from migration. Cultural and migration maps offer a comparative and diachronic insight into migration impulses and waves.Migration of ideas and techniques is also examined through artifacts resulting from forced or intended movement of people and experts. Two contemporary plays evolved from the stories of migrants/refugees offer probing and open-ended speculation about itinerancy, vagrancy, resettlement and economic emigration as part of social plurality. The tangible, visceral qualities of expression may shed light on issues too complex for verbal theory only. Approached is comparative examination of stylization in art and abstraction in theoretical inquiry. Asking: What kind of procedures and institutions retain connection to the vitality of the samples studied or portrayed? Proposing inquiry not only focused on issues in the world but also on how they are represented, measured and defined.